Shape complexity and process energy consumption in electron beam melting: a case of something for nothing in additive manufacturing? - Baumers, Martin; Tuck, Christopher; Wildman, Ricky D.; Ashcroft, Ian; Hague, Richard J.M. (Wiley for Yale University, 2016)
Additive manufacturing (AM) technology is capable of building up component geometry in a layer-by-layer process, entirely without tools, molds, or dies. One advantage of the approach is that it is capable of efficiently creating complex product geometry. Using experimental data collected during the manufacture of a titanium test part on a variant of AM technology, electron beam melting (EBM), this research studies the effect of a variation in product shape complexity on process energy consumption. This is done by applying a computationally quantifiable convexity-based characteristic associated with shape complexity to the test part and correlating this quantity with per-layer process energy consumption on the EBM system. Only a weak correlation is found between the complexity metric and energy consumption (ρ = .35), suggesting that process energy consumption is indeed not driven by shape complexity. This result is discussed in the context of the energy consumption of computer-controlled machining technology, which forms an important substitute to EBM. This article further discusses the impact of available additional shape complexity at the manufacturing process level on the incentives toward minimization of energy inputs, additional benefits arising later within the product’s life cycle, and its implications for value creation possibilities.